Pemberlakuan Kurikulum Berbasis Nilai dan Karakter dalam Pembelajaran Pendidikan Agama Kristen Terhadap Kecerdasan Spiritual Siswa SMA Negeri Di Tana Toraja. - Syani Bombongan Rantesalu (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2020)
Abstract: A value and character based curriculum is the core of the curriculum from time to time which is designed to answer the challenges of the times. In this paper, the author wants to examine the application of value-based and character-based curriculum in Christian Religious Education learning to the spiritual intelligence of public high school students in Tana Toraja. This is considered important because in the implementation of a value-based and character-based curriculum it has less impact on the spiritual intelligence of state high school students in Tana Toraja. The method used in this paper is qualitative research with descriptive analysis method. This study concludes that the curriculum developed in Christian religious education learning is still general in nature, which is designed in general in a universal context which is then developed according to a particular context. The curriculum in the context of Christianity in learning values and character in Christian education is only one source, namely from the Bible and applies to everyone in all places, as for the value in character building in relation to this spiritual intelligence, namely the value of love which is the main command of God, readiness to hear. and slow to speak, the value of holiness is not defiling oneself with various temptations and the values of the fruit of the Holy Spirit, namely love, joy, peace, patience, generosity, kindness, loyalty, gentleness and self-control.Keywords: values, character, spiritual intelligence  Abstrak: Kurikulum berbasis nilai dan karakter adalah inti dari dari kurikulum dari masa ke masa yang di desain untuk menjawab tantangan jaman. Dalam tulisan ini, penulis ingin mengkaji pemberlakuan kurikulum berbasis nilai dan karakter dalam pembelajaran Pendidikan Agama Kristen terhadap Kecerdasan spiritual siswa SMA Negeri di Tana Toraja. Hal ini dianggap penting oleh karena dalam pemberlakuan kurikulum berbasis nilai dan karakter kurang berdampak bagi kecerdasan spiritual siswa SMA Negeri di Tana Toraja. Dalam tulisan ini menggunakan metode kualitatif dengan analisis dekriptif. Penelitian ini menyimpulkan bahwa, kurikulum yang dikembangkan dalam pembelajaran pendidikan Agama kristen masih bersifat umum, yakni dirancang secara umum dalam konteks universal yang kemudian dikembangkan sesuai konteks tertentu. Kurikulum dalam konteks kekristenan dalam pembelajaran nilai dan karakter pada pendidikan Kristen hanya satu sumber yakni dari Alkitab dan berlaku bagi setiap orang disegala tempat, adapun nilai dalam pembentukan karakter dalam kaitannya dengan kecerdasan spiritual ini yakni nilai kasih yang merupakan perintah utama Tuhan Allah, kesiapan untuk mendengar dan lambat untuk berkata-kata, nilai kekudusan yakni tidak menajiskan diri dengan berbagai godaan jasmani dan nilai-nilai dari buah Roh Kudus Kata Kunci: Nilai, karakter, kecerdasan spiritual